Analysis of Occupational Noise in Association with Blood Pressure Among Workers at Geothermal Power Plant - Muhyidin Muhyidin; Sjahrul Meizar Nasri (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
The purpose of this study will analyze noise intensity at a geothermal power plant and its association with employees’ blood pressure and risk of hypertension. A cross-sectional survey using questionnaire as primary data; noise dosimeter, body mass index and blood pressure measurement records as secondary data. Total 101 workers participated by purposive sampling based on a similar exposure group (SEG). Mann-Whitney & χ2 test analysis was applied to examine the association of dependent variables and independent variables. Noise intensity was measured from the noise dose result during 8 working hours. Subjects with noise dose >80 dBA had higher levels of SBP / systolic blood pressure (119.1±11.2 mmHg) and DBP / diastolic blood pressure (75.6±5.3) than subjects with noise dose ≤80 dBA (SBP: 117.9±6.6 mmHg, DBP: 75.0±5.1). The hypertension prevalence was 7.9% at participants with noise dose >80 dBA and 2.6% in noise dose ≤80 dBA. The odds ratio (OR) of noise dose >80 dBA (OR = 3.190, 95% CI = 0.358-28.394), and smoking (OR = 2.469, 95% CI = 0.416-14.645). Noise intensity was not associated with SBP (p-value = 0.664), DBP (p-value = 0.538), and hypertension (p-value = 0.405). This study was the pioneer in the geothermal industry with noise dosimetry measurement. Further comprehensive studies need to be conducted to confirm the association between noise intensity and blood pressure and the risk of hypertension.